The improvement of judicial protection of marine environment in China: based on the analysis of 2,443 judicial cases - Liu, Xi; Liu, Sijie; Wang, Yuting (Frontiers in Marine Science, 2024)
With the proliferation of human activities, a series of marine ecological and environmental problems have arisen. Judicial application is important to test legislative achievements, explore judicial difficulties, and examine the compliance with the law. There is no case law in China and the impact of judicial decisions on the protection of marine environment is therefore indirect. Judicial decisions can reflect the implementation of the Marine Environmental Protection Law and play a crucial role in improving the marine environmental protection. An analysis of 2,443 cases related to marine environmental protection heard by courts at all levels across China from 1 January 2019 to 31 December 2023 has been conducted. The findings indicate an overall downward trend in cases related to marine environmental protection, suggesting positive governance outcomes to some extent. However, certain problems remain in the judicial protection of marine environment. Therefore, legislative efficiency should be properly increased and an independent crime for marine environmental pollution should be introduced to further clarify the legal bases for marine environmental protection. The intelligent trial assistance technology should also be applied to shorten trial time, improve trial efficiency, and unify judicial rules. The People’s Courts should play an active role in the provision of evidence and specific evidentiary burden provisions for different types of marine environmental pollutions should be proposed. The data sharing channels between various systems should be facilitated and the functionality for case referral should be developed for the coordination of administrative enforcement and criminal justice within a unified administrative enforcement platform.